Plasma‐Driven in Situ Production of Hydrogen Peroxide for Biocatalysis - Abdulkadir Yayci; Álvaro Gómez Baraibar; Marco Krewing; Elena Fernández‐Fueyo; Frank Hollmann; Miguel Alcalde; Robert Kourist; Julia E. Bandow (2020)
Peroxidases and peroxygenases are promising classes of enzymes for biocatalysis because of their ability to carry out one-electron oxidation reactions and stereoselective oxyfunctionalizations. However, industrial application is limited, as the major drawback is the sensitivity toward the required peroxide substrates. Herein, we report a novel biocatalysis approach to circumvent this shortcoming: in situ production of H2 O2 by dielectric barrier discharge plasma. The discharge plasma can be controlled to produce hydrogen peroxide at desired rates, yielding desired concentrations. Using horseradish peroxidase, it is demonstrated that hydrogen peroxide produced by plasma treatment can drive the enzymatic oxidation of model substrates. Fungal peroxygenase is then employed to convert ethylbenzene to (R)-1-phenylethanol with an ee of >96 % using plasma-generated hydrogen peroxide. As direct treatment of the reaction solution with plasma results in reduced enzyme activity, the use of plasma-treated liquid and protection strategies are investigated to increase total turnover. Technical plasmas present a noninvasive means to drive peroxide-based biotransformations.